ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NON PERFORMING FINANCING PADA PERBANKAN SYARIAH DI INDONESIA TAHUN 2011-2016 - Vanni, Kartika Marella; Rokhman, Wahibur (EQUILIBRIUM, 2017)
This study was conducted to examine the factors affecting Non Performing Financing (NPF) in Sharia Banking in Indonesia such as: Financing to Deposit Ratio (FDR), Exchange Rate, and Inflation. The data used in this research is obtained from the Publication Report on the official website of the Financial Services Authority and Bank Indonesia within a period of six years. This research uses multiple linear regression analysis model which is processed through Eviews 7.0 application. The result of hypothesis testing shows that Financing to Deposit Ratio (FDR) has negative and significant effect to Non Performing Financing (NPF), the exchange rate has positive and significant influence to Non Performing Financing (NPF), inflation have positive and non significant effect to Non Performing Financing (NPF), and Financing to Deposit Ratio (FDR), Exchange Rate, and Inflation together have significant influence to dependent variable that is Non Performing Financing (NPF).